Contemporary Reflections - a Study About Dinorath Do Valle's Chronicles in the Sao Jose Do Rio Preto Press (1943 - 1956) - Guimaraes Rezende, Vera Lucia [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2018)
Literary genre related to national circulation newspapers, mainly located on Brazilian capital cities, the chronicle was also present in the publishing scenario at the countryside in the mid-20th century, which includes Sao Jose do Rio Preto, the largest city of Sao Paulo's northwest, 414 kilometers distant from the state capital. This paper presents the first phase chronicles from the professor, and writer, Dinorath do Valle, gathered from newspapers' pages between 1943 and 1956. In addition to the historiographic recovery from Dinorath do Valle's works, this paper highlights the selected topics as well the approaches to these topics that at that time already indicated a critical view and a sharp language. These writings also request for a detailed study because they represent the first steps from this upcoming writer development on her literary structure technique, revealed decades later, when she was awarded 14 national and international contests.
Keywords: Chronicle; Dinorath do Valle; History; Journalism; Litterature; Sao Jose do Rio Preto